THE INFLUENCE OF MOTIVATION, WORK DISCIPLINE, AND THE EFFECTIVENESS OF JOB ROTATION ON THE PERFORMANCE OF EMPLOYEES IN THE DEPARTMENT OF TRANSPORTATION BATAM CITY - Nanda Purwantini; Mauli Siagian (Jurnal Ekonomi, 2023)
This research was conducted to see the effect of motivation, work discipline, and the effectiveness of job rotation on the performance of Batam City Transportation Department employees. The method in this study used quantitative methods with SPSS 26 statistical tools in associative (casual) form by distributing questionnaires to obtain data. The population in this study were employees who worked at the Batam City Transportation Service as many as 140 respondents using probability sampling and the slovin technique as a sample determination to 104 respondents. Testing the quality of the data using the validity test and reliability test, testing the classical assumptions using the normality test, multicollinearity test and heteroscedasticity test and influence test using multiple linear regression analysis and analysis of the coefficient of determination (R 2 ) . Furthermore, to test the hypothesis using the t test and f test. The results of this study indicate that motivation, work discipline, and effectiveness of job rotation have a positive and significant effect both partially and simultaneously on employee performance. The results of the coefficient of determination test (R 2 ) show that motivation, work discipline, and the effectiveness of job rotation have an effect of 66.7% on employee performance, while the remaining 33.3% are influenced by other variables outside this study.